Flow Pattern Identification and Pressure Drop Calculation for Gas-Liquid Flow in a Horizontal Pipeline - Fathollah Farhadi; S. Eliyassi (Iranian Journal of Chemistry & Chemical Engineering, 1989)
Two phase gas-liquid flow pattern in a horizontal pipeline is predicted very accurately using a newly-developed analytical relation. The pattern identification is based on one of the most widely used graphs, the Baker diagram, modified in a way that compensates for the unrealistic oversimplifications of recent works. The Kern's method of pressure drop calculation is used to obtain the frictional pressure drop in a gas-liquid pipeline flow. An interactive computer program is developed for the prediction of the flow pattern and calculation of pressure drop.